2012
DOI: 10.3996/032012-jfwm-027
|View full text |Cite
|
Sign up to set email alerts
|

Combining Field Data With Computer Simulations to Determine a Representative Reach for Brook Trout Assessment

Abstract: Fisheries biologists often use backpack electrofishing to sample stream fish. A common goal of sampling is to estimate density and/or biomass to make inferences about the status and trends of fish populations. One challenge when estimating population size is determining an appropriate site or reach length to sample. In this study, we empirically determined the required length of stream that needs to be sampled, assuming the study design is one site per stream, in order to achieve a desired level of accuracy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Our results showed that estimating the population or biomass with increasing precision required an extensive amount of sampling, regardless of how sections were chosen. In nearby Pennsylvania streams, 450 m of stream was required to effectively estimate Brook Trout populations to within 25% of the census size (Sweka et al 2012). Our results also agree with those of Bohlin et al (1989), suggesting that extensive survey is required to estimate trout abundance with enhanced precision.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our results showed that estimating the population or biomass with increasing precision required an extensive amount of sampling, regardless of how sections were chosen. In nearby Pennsylvania streams, 450 m of stream was required to effectively estimate Brook Trout populations to within 25% of the census size (Sweka et al 2012). Our results also agree with those of Bohlin et al (1989), suggesting that extensive survey is required to estimate trout abundance with enhanced precision.…”
Section: Discussionsupporting
confidence: 76%
“…The patchy distributions of stream fishes and their habitats may result in reaches that insufficiently characterize a population (Ensign et al 1997). Increasing the total survey area reduces extrapolation errors (Sweka et al 2012) but at the expense of additional cost. Using randomization to select reaches has become an established approach (Klauda et al 1998, and others).…”
mentioning
confidence: 99%
“…Fish sampling.-On each study stream, a 400-m study reach was established and multiple-pass backpack electrofishing was conducted to sample fish in the summer (July and August) of each year from 2010 to 2019. We chose a 400-m study reach because Sweka et al (2012) found this reach length to be representative in estimating Brook Trout density and biomass within 25% of the true density and biomass. Electrofishing proceeded in an upstream direction with a two-person crew; one person operated the backpack electrofisher equipped with a handheld anode and rat-tail style cathode and handled a dip net, while the other person handled a dip net and a bucket to hold captured fish.…”
Section: Methodsmentioning
confidence: 99%
“…2006), but sampling of such a large reach as we did (400 m) ensured that large numbers of Brook Trout were collected and that this bias was minimized (Sweka et al. 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation